Using Indicators to Assess Climate Change Vulnerabilities: Are There Lessons to Learn for Emerging Loss and Damage Debates?. Issue 1 (January 2014) - Vincent, Katharine; Cull, Tracy
Abstract Climate change is one of the most pressing global issues. The United Nations Framework Convention on Climate Change is committed to supporting adaptation in developing countries but identifying priority needs depends on an assessment of vulnerability. Indicators and indices are one common method for vulnerability assessments. A variety of vulnerability indicators and indices have been created for global level, cross‐country comparison within regions and also at sub‐national level, and as a result of these indicators, a variety of methodological critiques have arisen. This paper reviews vulnerability science and the evolution of indicators for vulnerability assessment and then assesses whether there is utility in using indicators for assessing the risk of loss and damage – one of the latest thrusts of the international policy negotiations.